2011
DOI: 10.3892/or.2011.1199
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring peri-operative immune suppression in renal cancer patients

Abstract: Abstract. The aim of this study was the identification of surrogate markers of host immunity in renal cell carcinoma (RCC) patients. Using 4-color flow cytometry the immunophenotype of blood immune cells of RCC patients was compared to that of healthy volunteers and correlated with staging and grading of patients. Furthermore, the time course of these immune markers was compared in RCC patients undergoing either open surgery or laparoscopy. Compared to the healthy control group, blood of RCC patients contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Moreover, the large number of pretreatment monocytes was associated with poor prognosis in lymphoma and other solid tumors [19], [44], [45]. Supportively, our results showed that the higher monocyte count was significantly associated with poor survival in NPC patients and it was an independent factor for prognosis prediction.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the large number of pretreatment monocytes was associated with poor prognosis in lymphoma and other solid tumors [19], [44], [45]. Supportively, our results showed that the higher monocyte count was significantly associated with poor survival in NPC patients and it was an independent factor for prognosis prediction.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, an increased number of monocytes before treatment has been associated with poor prognosis of lymphoma and other solid tumors [18, 19]. The results of this study also showed that a relatively high LMR was associated with better survival in NPC.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, tumors with loss of HLA class Ia expression often express HLA-G and/or HLA-E thereby evading both CTL and NK cell recognition. Despite a high frequency of T cell infiltration significantly correlated to HLA-G expression a reduced patients’ survival was found [27, 37, 38]. Regulatory FoxP3 + T cells (Treg) have immune suppressive activity by inhibiting host anti-tumor responses.…”
Section: Discussionmentioning
confidence: 99%